Durability Performance Analysis of Mixture Asphalt Concrete - Base Course (AC-Base) Using Coal Fly Ash as A Filler Substitute - Archenita, Dwina; Alkhairi, Wafiq; Rizki, Aditiya; -, Apwiddhal; -, Satwarnirat (SOTVI, 2023)
Highways are land transportation infrastructure whose needs in Indonesia continue to increase, along with the increasing number of vehicle. The top Laston or base coarse (AC-Base) is a pavement foundation consisting of a mixture of asphalt aggregates with a certain ratio mixed and compacted in a hotmix. This coarse is at under binder coarse (AC-BC), not directly related to the weather, but it needs to have stability to withstand the traffic load spread through the vehicle wheels. Base coarse (AC-Base) serves to provide support the surface coarse, reduce strain and stress, spread and continue the load of road construction to the layer below (subgrade). Filler as one of the materials forming the AC-Base layer usually obtained from stone ash whose availability is increasingly difficult to feel in the field implementation. Therefore, a substitute material or substitute material is needed for the filler. One possible substitute material is fly ash. This research will analyze the performance of AC-Base coarse that make use of filler substitution material using fly ash with variation FA-0%, FA-5%, FA-7.5%, FA-10%, FA-12.5% and FA-15%. The samples made by Marshall Method will give the Optimum Asphalt Content (OAC) value on each mix variation. While the performance of this AC-Base mixture in increasing density, durability, and stability in the pavement mixture using the Marshall Immersion method (MI). The analysis result shows that the OAC value at 0% fly ash variation is 6,82%, at 5% fly ash variation is 6,87%, at 7.5% fly ash variation is 6,85%, at 10% fly ash variation is 6,84%, at 12.5% fly ash variation is 6,82%, and at 15% fly ash variation is 6.79%. While the performance of AC-Base mixture indicated by the MI value meets the specifications, and the MI value obtained tends to increase along with the increase in the percentage of fly ash. The mixture with 15% fly ash shows the better durability performance (99,75%) compared to other variations 0%, 5%, 7,5%, 10% and 12,5% (96,44%, 97,51%, 97,71%, 98,36% and 99,54%).